Effects of sodium dodecylbenzene sulfonate (SDBS) on zebrafish (Danio rerio) gills and blood - Libanio Reis Santos, Eduardo [UNESP]; Silva, Odaiza [UNESP]; Nascimento Araújo, Bruna Jéssyca [UNESP]; de Lima Rodrigues, Milena [UNESP]; de Oliveira-Lima, Jeffesson; Camargo-Mathias, Maria Izabel [UNESP] (Taylor & Francis, 2024)
Sodium dodecylbenzene sulfonate (SDBS) is an important surfactant used as a cleaning agent and industrial additive to remove unwanted chemicals which have been detected in the aquatic environment. The aim of this study was to examine the toxicological potential of SDBS on the gills of adult male zebrafish (Danio rerio) exposed to this chemical. For the 96 hr acute exposure, fish were divided into three groups: control, 0.25 mg/L, and 0.5 mg/L of SDBS. After the experiment, morphophysiological analyses (gill histopathology and histochemistry), oxidative stress (determination of gill activities of superoxide dismutase (SOD) and catalase (CAT)), and hematological analyses (leukocyte differentiation) were conducted. Data demonstrated that SDBS at both tested concentrations altered the histopathological index and initiated circulatory disturbances, as well as adverse, progressive, and immunological changes in the gills. In the 0.5 mg/L group, SOD activity decreased significantly, but CAT activity was not altered. Prominent blood changes observed in this group were neutrophilia and lymphocytosis. The number of mucous and chloride cells increased significantly in both groups. Taken together, our findings demonstrated that exposure of D. rerio to SDBS, even for 96 hr, produced adverse morphological and hematological effects associated with a reduction in SOD activity. Our findings indicate that exposure of aquatic species to the anionic surfactant SDBS may lead to adverse consequences associated with oxidative stress. Therefore, this study highlights the risks that this substance may pose to aquatic ecosystems and emphasizes the need for further investigations and strict regulations on its disposal.
Keywords: Anionic surfactant; Danio rerio; glycoproteins; histopathology; morphology; oxidative stress